Investigation of phase and power fluctuation events using Rytov method and the forward propagation model - Vaggu, Pralay Raj; Bust, Gary; Deshpande, Kshitija; Datta-Barua, Seebany; Zettergren, Matthew (Frontiers in Astronomy and Space Sciences, 2025)
Ionospheric density irregularities cause fluctuations in transionospheric satellite signals, known as “scintillation”. While scintillation degrades the performance of navigation satellites, such as the Global Positioning System (GPS), it also serves as a diagnostic tool for studying the underlying plasma processes. In this study, we characterize high-latitude ionospheric structuring and its impact on radio signals using a 3D propagation model, the “Satellite-beacon Ionospheric-scintillation Global Model of the upper Atmosphere” (SIGMA), in conjunction with GPS observations and an analytical model. Establishing a modeling framework for defining the irregularity parameters, including spatial extent, spectral index, axial ratios, density fluctuations, layer height, drift velocity, and thickness, is essential for providing insights into scintillation modeling. We use the Rytov method, a well-known analytical 2D model for estimating irregularity parameters from observed log-power and phase spectra, which is particularly useful in the absence of auxiliary observations. Observations from GPS array receivers in Poker Flat, Alaska, are used to examine the simultaneous occurrence of phase and power fluctuations. These occurrences are rare, as only a few such events were detected in observations from 2014 to 2019. These reveal both large-scale, refractive fluctuations and smaller-scale, diffractive features embedded within them, highlighting the multiscale nature of plasma structuring. Initializing SIGMA with Rytov-derived parameters shows a good agreement between the simulated and observed power spectral densities, with goodness-of-fit metric (χ′) close to 1. This is observed with power fluctuations, particularly when shorter temporal segments are used for the inversion. A spectral break within the diffractive regime suggests the presence of multiscale structuring. Overall, our findings support the concept that turbulent energy cascading from large-scale structures, likely driven by gradient-drift and/or Kelvin–Helmholtz instabilities, plays a crucial role in generating scintillation-inducing irregularities.